Fiscal Decentralization Improves Social Outcomes When Countries Have Good Governance - Nakatani, Ryota (IMF Working Papers; Working Paper ;, 2022)
Does fiscal decentralization improve health and educational outcomes? Does this improvement depend on the quality of governance? How do fiscal decentralization and governance interact? We answer these questions through an instrumental variable Tobit analysis of cross-country panel data. We find negative effects of fiscal decentralization on health outcomes, which however are more than offset by better governance. Education expenditure decentralization to subnational governments enhances educational outcomes. We conclude that countries can only reap the benefits from decentralization when the quality of their governance arrangements exceeds a certain threshold. We also find that sequencing and staging of decentralization matter. Countries should improve government effectiveness and control of corruption first to maximize benefits of fiscal decentralization.